Trichoepithelioma (TE) with Aggressive Characters: A Case Report - Erhoma, Bashir (The Libyan Journal of Science, 2015)
Trichoepithelioma (TE) is a benign adnexal neoplasm that may be of superficial form. The gene associated with TE links to short arm of chromosome 9p21. The gene for the development of familial trichoepithelioma also encodes for tumor suppressor gene. Its altered cellular proliferation may be up-regulated because of a poorly functioning or absent tumor suppressor gene. This is due to presence of significant numbers of Merkel cells within the tumor nest and the detection of a sheath of CD34 positive dendrocytes around the tumor nests. It appears that TE differentiates towards or derives from hair structure, particularly the hair bulge. TE is reported with equal frequency in male and female. TE is seen in young age adults. The hereditary form, however, may be seen in younger individuals. Here wereport a case of TE with aggressive characters, studied with histopathology and immunohistochemistry, that shows unusual aggressive features manifested by high mitotic index. This case is reported to alert the pathologist and clinician to the existence of such lesion.